Refractory castables for titanium metallurgy based on calcium zirconate. (15th June 2018) - Schafföner, Stefan; Qin, Ting; Fruhstorfer, Jens; Jahn, Constantin; Schmidt, Gert; Jansen, Helge; Aneziris, Christos G.
Abstract: Calcium zirconate (CaZrO3 ) is a promising refractory material to melt titanium alloys. Therefore the present study investigated refractory castables based on CaZrO3 to allow an upscaling to larger melting crucibles and refractory linings. The study first included the processing optimization of the refractory castable containing calcium aluminate cement using a full factorial experimental design. Then the physical, chemical, mechanical and thermomechanical properties that determine the practical application of the castable were analyzed. The properties were generally similar to the ones of uniaxially pressed refractories based on CaZrO3 . Nevertheless, the matrix containing calcium aluminates caused a pronounced sintering shrinkage leading to a smaller apparent porosity and a lower refractoriness compared to uniaxially pressed refractories. Finally, melting crucibles with an inner volume of 900 ml were successfully manufactured. Thus, this study provides an effective framework for the further development of large CaZrO3 refractories. Graphical Abstract: Highlights: Refractory castables based on calcium zirconate for the metallurgy of titanium alloys are presented for the first time. Calcium aluminate binders provide a fast processing and sufficient refractoriness for medium-sized melting crucibles. The whole range of the development of the castables including microstructural, mechanical and thermomechanical characterization is described. The developed castables using high melting perovskites are an important step for the industrial implementation of refractories for titanium metallurgy.